2021
DOI: 10.1039/d0sc06132h
|View full text |Cite
|
Sign up to set email alerts
|

A rationally designed two-dimensional MoSe2/Ti2CO2 heterojunction for photocatalytic overall water splitting: simultaneously suppressing electron–hole recombination and photocorrosion

Abstract: The two challenges of electron–hole recombination and photocorrosion for two-dimensional transition metal dichalcogenides in the application of photocatalytic water splitting are simultaneously suppressed by rational design of heterojunctions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(65 citation statements)
references
References 48 publications
4
61
0
Order By: Relevance
“…Various type-II heterojunctions have been reported with different materials interface stacking to show charge separation as photocatalysts for splitting water [ 205 , 206 , 207 , 208 , 209 , 210 , 211 , 212 , 213 , 214 , 215 ]. A novel SiH/CeO 2 (111) type-II heterojunction with the six stacking modes was constructed with optimized structures ( Figure 10 a) having a slight lattice mismatch of less than 1% [ 216 ].…”
Section: Engineering Of 2d Materials For Enhanced Photocatalytic Surf...mentioning
confidence: 99%
“…Various type-II heterojunctions have been reported with different materials interface stacking to show charge separation as photocatalysts for splitting water [ 205 , 206 , 207 , 208 , 209 , 210 , 211 , 212 , 213 , 214 , 215 ]. A novel SiH/CeO 2 (111) type-II heterojunction with the six stacking modes was constructed with optimized structures ( Figure 10 a) having a slight lattice mismatch of less than 1% [ 216 ].…”
Section: Engineering Of 2d Materials For Enhanced Photocatalytic Surf...mentioning
confidence: 99%
“… 42 In addition, inherent photocorrosion associated with 2D TMDCs also greatly limits the application of MoSe 2 in photocatalytic H 2 generation. 43 Therefore, rather than developing MoSe 2 as a standalone alternative to popular catalysts (e.g., TiO 2 ) for photolysis, more focus was allocated to utilize MoSe 2 in combination with other electron-generating materials as it provides active sites for H 2 generation and acts as an efficient electron sink. Gupta et al 42 reported the photocatalytic HER activity of 1T-MoSe 2 sensitized by Eosin Y dye.…”
Section: Mose 2 In Photocatalytic Hydrogen Generationmentioning
confidence: 99%
“…Time-dependent population of photogenerated (b) holes and (c) electrons in the CB and VB of MoSe 2 and Ti 2 CO 2 . Reprinted with permission from ref ( 43 ). Copyright 2021 Royal Society of Chemistry.…”
Section: Mose 2 In Photocatalytic Hydrogen Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…Photoelectrochemical (PEC) analysis, as a thriving analytical technique, not only has the merits of simple operation and low cost but also possesses the advantages of low background noise and high sensitivity owing to the total separation of excitation light source and the detection signal, gathering tremendous attention in recent years. As is well known, the photoelectric conversion efficiency of the photoactive material makes great difference on the performance of PEC biosensors. , Reducing the electron–hole pair recombination probability and enhancing the light absorption in the ultraviolet–visible (UV–vis) region are effective ways to promote the photoelectric conversion efficiency of photoelectric material . Unfortunately, single photoelectric materials usually have the disadvantage of low photoelectric conversion efficiency, which limits their practical applications. , In recent years, the construction of heterojunctions is considered to be a feasible and effective way to facilitate the electron–hole separation and restrain the recombination of electron–hole of optoelectronic materials. For instance, Xiong’s group synthesized a ZnO/CeO 2 Z-scheme heterojunction for photodegradating rhodamine B . Lately, Niu’s group constructed a MoS 2 /ZnO p–n heterostructure for propyl gallate determination .…”
Section: Introductionmentioning
confidence: 99%